2022
DOI: 10.3390/pathogens11080884
|View full text |Cite
|
Sign up to set email alerts
|

Anthracnose of Onion (Allium cepa L.): A Twister Disease

Abstract: The onion (Allium cepa L.) is a lucrative and high-value vegetable–spice crop in India, but it is sensitive to several of diseases caused by fungi, bacteria, viruses, and nematodes, of which a fungal disease, anthracnose, caused by Colletotrichum spp., is a major issue for both onion producers and researchers since it severely affects the bulb production. Twister disease is currently one of the most common problems in onion production, particularly in humid regions, and it reduces productivity while also lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 61 publications
0
9
0
2
Order By: Relevance
“…However, the study identified another alternative, Tajuk, which showed lower severity, compared with the other genotypes, up to five weeks after inoculation. As reports on Sumenep not producing a flower that might cause a problem in the utilization as a source of resistance for breeding (Dutta et al, 2022), the partial resistance found in Tajuk could be useful and noteworthy, in addition to fungicide application to control C. gloeosporioides.…”
Section: Screening Testmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the study identified another alternative, Tajuk, which showed lower severity, compared with the other genotypes, up to five weeks after inoculation. As reports on Sumenep not producing a flower that might cause a problem in the utilization as a source of resistance for breeding (Dutta et al, 2022), the partial resistance found in Tajuk could be useful and noteworthy, in addition to fungicide application to control C. gloeosporioides.…”
Section: Screening Testmentioning
confidence: 99%
“…Later, the infection moves to the neck region or above the basal plate. Further, the symptoms superficially will appear on bulbs, spread to inner tissue, causing deformation and rotting of the bulb, and in the worst case, continue to complete death of the plant (Dutta et al, 2022). Since the leaf infection could result in yield reduction and rotting of bulbs during and after storage, the resistance properties in the shallot leaves are most relevant, determining the success of shallot production.…”
Section: Leaf Anatomical Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Jamur terutama menginfeksi pada daun atau bagian tanaman yang lemah, memproduksi berbagai macam struktur infeksi seperti konidia, acervulus, seta dan apresoria selama proses infeksi pada proses interaksi inang dan patogen (Gautam, 2014). Gejala awal dari penyakit ini adalah bercak berwarna hijau muda kekuningan atau berupa bercak kecil berwarna putih (Galvan et al, 1997;Dutta et al, 2022). Gejala khas yang nampak pada tanaman yaitu daun menguning, melengkung, berlekuk, klorosis dan malformasi pada leher daun.…”
Section: Gejala Antraknosa (Busuk Daun)unclassified
“…Gejala khas yang nampak pada tanaman yaitu daun menguning, melengkung, berlekuk, klorosis dan malformasi pada leher daun. Gejala lanjut menyebabkan akar tanaman menjadi lebih sedikit dan lebih pendek dibanding pada tanaman sehat, kemudian tanaman akan mati (Dutta et al, 2022;Sarianti dan Subandar, 2022). Infeksi biasanya muncul pada daun yang lebih tua, serangan lanjut menyebabkan daun layu dan mati (Galvan et al, 1997).…”
Section: Gejala Antraknosa (Busuk Daun)unclassified